Development of PV array configuration under different partial shading condition - Mohammad Syahir Bin Ishak; Rahmatul Hidayah Salimin; Ismail Musirin; Zulkiffli Abdul Hamid (Institute of Advanced Engineering and Science, 2019)
This paper investigates the performances of different photovoltaic (PV) array under several shading condition. Four types of photovoltaic array configuration scheme which are ‘Series’ (S), Series-Parallel’ (SP), Total-Cross-Tied’ (TCT), and ‘Bridge-Link’ (BL) array topologies were tested by applying a 6x6 PV array under 6 different shading scenarios. The modeling is developed using Matlab/Simulink. The performances and output characteristics of photovoltaic array are compared and analyzed. System engineer can use the detailed characteristics of different array configuration to approximate the outcome power and pick the best configuration of the system by concerning the current natural condition to enhance the overall efficiency.